Manajemen Risiko terhadap Kontrak Perencanaan Konstruksi Jalan Tol dengan Metode Simulasi Monte Carlo - Sutedi, Luthfi Maulana; Purwanto, Hari (Journal of Infrastructure Policy and Management (JIPM), 2023)
The XYZ Toll Road Section Project experienced contract failure due to multiple changes in the planning contract (addendum), resulting in disruptions to the implementation process and the failure to meet the overall project completion target. The objective of this research is to analyze the potential risks that led to contract failure and propose mitigation efforts for each identified risk. The method employed is the Monte Carlo Simulation, providing a comprehensive approach through empirical data from questionnaires and simulation results to enhance the accuracy of the analysis. This study identified 9 high-level risks and 4 medium-level risks based on risk analysis and categorization on the risk map. The research also strives to implement mitigation measures for each risk based on the prioritized risk values, from highest to lowest, as a form of risk management. This approach aims to minimize the likelihood of contract failure and enhance the operational efficiency of the project.